Unemployment fluctuations and the predictability of currency returns - Nucera, Federico (Journal of Banking & Finance, 2017)
We investigate whether unemployment fluctuations generate predictability in the cross-section of currency excess returns. We find that currencies with lower growth in the unemployment rate appreciate while currencies with higher growth in the unemployment rate depreciate. As a result, an investment strategy that involves investing in the former and short selling of the latter produces positive and sizable excess returns. Asset pricing tests show that the predictability is not driven by exposure to traditional risk factors such as global equity risk, global foreign exchange volatility risk, and downside risk but is related instead to an idiosyncratic unemployment risk.